Early increment of soluble triggering receptor expressed on myeloid cells 2 in plasma might be a predictor of poor outcome after ischemic stroke. (March 2020) - Kwon, Hyuk Sung; Lee, Eun-Hye; Park, Hyun-Hee; Jin, Jeong-Hwa; Choi, Hojin; Lee, Kyu-Yong; Lee, Young Joo; Lee, Jae-Hong; de Oliveira, Felipe Marques Souza; Kim, Hyun Young; Seo Kim, Young; Kim, Bum Joon; et al.
Highlights: Microglia are activated after ischemic stroke and sTREM2 levels are considered to reflect the activation of microglia. Early increment of sTREM2 and late decrement of sTREM2 were more common in patients with poor outcome after ischemic stroke. Early increment of sTREM2 were independently associated with poor outcome after ischemic stroke. Abstract: Soluble triggering receptor expressed on myeloid cells 2 (sTREM2) is derived from cleavage of TREM2, which is expressed on the cell surface of microlgia and other tissue-specific macrophages. In the present study, the changes in the sTREM2 levels after ischemic stroke (IS) and their association with clinical outcomes were evaluated. A total of 43 patients diagnosed with non-cardioembolic IS between June 2011 and May 2014 were consecutively included in this study. Patients treated with intravenous thrombolysis or intra-arterial thrombectomy were excluded. Plasma samples were collected three times (days 1, 7, and 90) after ictus. The sTREM2 level was measured in the samples using the highly sensitive solid-phase proximity ligation assay (SP-PLA). Among the 43 subjects, higher initial NIH stroke scale (NIHSS) score ( P  = 0.005), early increment of sTREM2 ( P <  0.001), and late decrement of sTREM2 ( P  = 0.002), were more common in patients with poor outcome. Based on multivariate analysis, initial NIHSS score ( P  = 0.015) and early increment of sTREM2 ( P  = 0.032) were independently associated with poor outcome. The results from the present study indicate that increment of sTREM2 level at the early phase was a predictor of poor outcome. Serial follow-up of sTREM2 may aid prognosis after stroke.